Polish farms in the light of quality requirements - Bezat, Agnieszka (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2008)
After the accession of Poland to the European Union farmers have to fulfil high food quality requirements. In accordance with the requirement 172/2002 of the European Commission, they should keep documentation regarding their part in the product’s flow in the food chain. This paper focuses particularly on the analysis to what degree requirements are satisfied by the analysed farms. A cluster analysis and a point assessment technique were used